Peningkatan Membandingkan Dua Pecahan melalui Strategi Calilang pada Siswa Kelas VI SD Muhammadiyah 1 Babat - Dymas Zahruddin Azmy; Izza Eka Ningrum (FONDATIA, 2021)
This study aims to improve students' ability to understand fraction comparisons of sixth graders at SD Muhammadiyah 1 Babat by using the CALILANG strategy. This type of research is classroom action research. The subjects in this study were students of class VI SD Muhammadiyah 1 Babat, totaling 10 students. Data collection techniques were carried out by observation, test, and documentary techniques. The research instrument used an observation sheet and a written test. The data analysis technique uses the mean formula whose results are presented in a qualitative descriptive form.